Palladium nanocluster / hydrotalcite nanocomposite as well as preparation method and application thereof

By loading palladium nanoclusters on copper magnesium aluminum hydrotalcite nanosheets, a palladium nanocluster/hydrotalcite nanocomposite material is prepared, which solves the problem of low efficiency of existing sonosensitizers under ultrasound and achieves efficient sonodynamic therapy and light therapy. Sound imaging effect.

CN119326908APending Publication Date: 2025-01-21TECHNICAL INST OF PHYSICS & CHEMISTRY - CHINESE ACAD OF SCI
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202310882592.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-07-18
Publication Date
2025-01-21

AI Technical Summary

Technical Problem

The existing sonic sensitizers are inefficient in electron and hole separation induced by ultrasound and stay in the body for a long time, which affects its safety and limits the development of sonic dynamic therapy.

Method used

The use of 簇 nanometer clusters/water talcum nano -composite materials is used as acoustic agents, and the vocal power effect is improved by using the two -dimensional limited domain effect and zero price of the zero price of copper, aluminum aluminum water talcum slices to improve the vocal power effect.

Benefits of technology

This composite material produces a large amount of active oxygen under ultrasound, consumes NADH, which causes mitochondrial dysfunction, significantly improves the effect of vocal power therapy, and has good light sound imaging performance and biological safety.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119326908A_ABST
    Figure CN119326908A_ABST
Patent Text Reader

Abstract

The invention discloses a palladium nanocluster / copper-magnesium-aluminum hydrotalcite nanocomposite as well as a preparation method and application thereof. The structure of the composite material comprises a copper-magnesium-aluminum hydrotalcite nanosheet and a palladium nanocluster loaded on the copper-magnesium-aluminum hydrotalcite nanosheet. The nano composite material has good photo-thermal performance, can realize photoacoustic imaging under irradiation of near-infrared light, can generate a large amount of active oxygen under ultrasonic action, and further consumes NADH (Nicotinamide Adenine Dinucleotide Hormone) for energy metabolism to cause mitochondrial dysfunction.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of preparation of anticancer drugs, and more specifically to a palladium nanocluster / hydrotalcite nanocomposite material and a preparation method and application thereof. Background Art

[0002] Cancer is one of the major threats to human health today, with a very high mortality rate. However, traditional cancer therapies such as surgical resection, radiotherapy, and chemotherapy have limited efficacy, high toxicity, and serious side effects. Therefore, in recent years, new treatment methods based on nanotechnology have been widely used in cancer treatment research, such as photothermal therapy, photodynamic therapy, sonodynamic therapy, and chemodynamic therapy (Chem. Soc. Rev., 2022, 51, 8201-8215). Among them, sonodynamic therapy uses ultrasound to excite sonosensitizers to react with oxygen or water to produce reactive oxygen species (ROS). At the same time, ultrasound can produce cavitation effects to produce strong shear forces that cause cancer cells to die. It is a novel, efficient, low-side-effect, and non-invasive technology for treating cancer. It can break through the tissue penetration depth limit of light in phototherapy and can achieve effective treatment of deep tumor tissues. In addition, the disordered vascular system, high osmotic pressure, and highly viscous extracellular matrix of tumor tissues hinder the entry of drug molecules into tumor cells. Ultrasound can improve the permeability of cell membranes, thereby increasing the enrichment of sonosensitizers in tumor cells and improving the therapeutic effect. The sonosensitizers widely reported at present are mainly organic sonosensitizers (such as porphyrin derivatives and phthalocyanines, etc.) and inorganic sonosensitizers (titanium oxide, etc.). Among them, the stability of organic sonosensitizers needs to be further improved. At the same time, most organic sonosensitizers are photosensitizers, and their phototoxicity poses certain problems in the process of tumor treatment. Inorganic sonosensitizers have high stability, but their sonosensitization efficiency is low, and their long-term retention in the body affects their safety. The limitations of these sonosensitizers have greatly restricted the development of sonodynamic therapy. Therefore, there is an urgent need to develop biodegradable, multifunctional and efficient sonosensitizers that respond to the tumor microenvironment (Nano Res. 2020, 13, 2898-2908).

[0003] As a unique two-dimensional layered supramolecular material, hydrotalcite (LDH) has two typical advantages in nanomedicine: first, the hydroxyl group is sensitive to acidic environment, resulting in the release of therapeutic drugs in a pH-responsive manner; second, the positive charge of the layer enables the material to effectively interact with the negatively charged cell membrane, thereby effectively delivering it within the cell. Moreover, due to the exchangeability of its interlaminar anions, it has a high drug loading capacity; at the same time, the cations of the layer can be reasonably adjusted to interact with non-cellular components in the tumor microenvironment and cause cancer cells to apoptosis. In addition, most of the components of LDH are minerals similar to silicate clay, without any obvious side effects, and can also be degraded in acidic environments, ensuring high biocompatibility. These excellent properties of hydrotalcite provide new ideas for the preparation of sonosensitizers with high biocompatibility and good sonosensitivity efficiency.

[0004] However, most of the existing hydrotalcite-based materials are used in photothermal therapy, photodynamic therapy and chemodynamic therapy, and there are few reports on their use as sonosensitizers for sonodynamic therapy. In addition, the efficiency of the currently reported hydrotalcite-based sonosensitizers still needs to be greatly improved, as their electron and hole separation efficiency induced by ultrasound is low and they are extremely easy to recombine. Summary of the invention

[0005] Based on the above facts, the purpose of the present invention is to provide a palladium nanocluster / hydrotalcite nanocomposite material and its preparation method and application, so that the composite material has excellent effect when used as a sonosensitizer or photoacoustic imaging agent. The nanocomposite material has good photothermal properties, can realize photoacoustic imaging under near-infrared light irradiation, and can generate a large amount of reactive oxygen under ultrasound, and further consume NADH used for energy metabolism to cause mitochondrial dysfunction.

[0006] In order to achieve the above object, the present invention adopts the following technical solutions:

[0007] In one aspect, the present invention provides a palladium nanocluster / hydrotalcite nanocomposite material, wherein the structure of the composite material comprises copper-magnesium-aluminum hydrotalcite nanosheets and palladium nanoclusters supported on the copper-magnesium-aluminum hydrotalcite nanosheets.

[0008] In the technical solution, the palladium nanoclusters are evenly distributed on the copper-magnesium-aluminum hydrotalcite nanosheets. At the same time, the loading of the palladium nanoclusters has no obvious effect on the morphology and size of the copper-magnesium-aluminum hydrotalcite nanosheets, and only slightly increases the thickness.

[0009] In this technical solution, the copper-magnesium-aluminum hydrotalcite nanosheets have good biosafety. The copper element is added to the magnesium-aluminum, and the interaction between copper and palladium can further regulate the distribution of electrons and improve the sonodynamic effect. In addition, palladium in the form of nanoclusters can cause most of the palladium to exist in a zero-valent form, which is conducive to the generation of holes.

[0010] Furthermore, the size of the composite material is 80-140 nm.

[0011] Furthermore, the average thickness of the composite material is 6-8 nm.

[0012] It should be noted that in the technical solution of the present invention, size refers to length.

[0013] Furthermore, the copper-magnesium-aluminum hydrotalcite nanosheets have a size range of 80-140 nm and a thickness of 1-3 nm, and are layered double metal hydroxides.

[0014] Furthermore, the size of the palladium nanoclusters is 5-8 nm.

[0015] Furthermore, in the copper-magnesium-aluminum hydrotalcite nanosheets, Cu 2+ Mg 2+ and Al 3+ The molar ratio of Cu is 0.1:2:1-1:2:1. At this time, the obtained composite material has good photoacoustic imaging and excellent sonodynamic therapy effect when used as a sonosensitizer or photoacoustic imaging agent. 2+ Mg 2+ and Al 3+ When the molar ratio is 0.1:2:1, the above effect is better.

[0016] Furthermore, in the composite material, the loading amount of palladium nanoclusters on the copper-magnesium-aluminum hydrotalcite nanosheets is 5-25wt%.

[0017] It should be noted that the above loading amount refers to the mass ratio of palladium nanoclusters to copper-magnesium-aluminum hydrotalcite nanosheets.

[0018] Furthermore, the chemical composition of the copper-magnesium-aluminum hydrotalcite nanosheets is [M Ⅱ 1-x M Ⅲ x( OH)2]A n- z / n ·yH2O, where M Ⅱ Cu 2+ and Mg 2+ and M Ⅲ Al 3+ ; x is M Ⅱ / (M Ⅱ +M Ⅲ ) molar ratio, ranging from 1 / 3 to 1 / 4, y is the amount of crystal water, A n- is the anion between the layers, which is NO in the present invention. 3- .

[0019] In another aspect, the present invention provides a method for preparing the composite material as described above, comprising the following steps:

[0020] The copper-magnesium-aluminum hydrotalcite nanosheets and the aqueous solution of sodium tetrachloropalladate are mixed evenly, and then alkaline sodium borohydride is added dropwise. After mixing evenly, the mixture is centrifuged, washed, and dried to obtain the composite material.

[0021] In the above preparation method, the use of sodium tetrachloropalladate helps to form a palladium nanocluster structure on the copper-magnesium-aluminum hydrotalcite nanosheets.

[0022] Furthermore, the mass ratio of the copper-magnesium-aluminum hydrotalcite nanosheets to sodium tetrachloropalladate is 5-25%.

[0023] Furthermore, the preparation of the copper-magnesium-aluminum hydrotalcite nanosheets comprises the following steps:

[0024] Adding copper nitrate hexahydrate, magnesium nitrate trihydrate, aluminum nitrate nonahydrate and an aqueous solution of sodium hydroxide dropwise to an aqueous solution of sodium carbonate simultaneously, so that the pH of the mixed solution is maintained at 9-10;

[0025] After stirring and reacting for 0.5-2h, the mixture is centrifuged, washed and dried to obtain the copper-magnesium-aluminum hydrotalcite nanosheets.

[0026] Furthermore, the stirring temperature is 80° C., and the stirring time is 0.5-2 h.

[0027] Furthermore, the molar mass ratio of the copper nitrate hexahydrate, the magnesium nitrate trihydrate and the aluminum nitrate nonahydrate is 0.1:2:1-1:2:1.

[0028] During the preparation of the copper-magnesium-aluminum hydrotalcite nanosheets, the pH of the mixed solution is maintained at 9-10, which is helpful for obtaining the copper-magnesium-aluminum hydrotalcite nanosheets.

[0029] In another aspect, the present invention provides a sonosensitizer, which is prepared from the composite material as described above.

[0030] In another aspect, the present invention provides use of the composite material as described above in preparing a sonosensitizer for tumor treatment.

[0031] In yet another aspect, the present invention provides use of the composite material as described above in preparing a photoacoustic imaging agent.

[0032] The beneficial effects of the present invention are as follows:

[0033] In the composite material provided in the present invention, palladium nanoclusters are uniformly loaded on copper-magnesium-aluminum hydrotalcite nanosheets. Due to the two-dimensional confinement effect of the copper-magnesium-aluminum hydrotalcite nanosheets, the singlet oxygen and superoxide radical generation efficiency of metal palladium can be effectively increased, and the divalent copper in the hydrotalcite is promoted to be converted into monovalent copper, generating more active oxygen, so that the composite material has photoacoustic imaging performance and exhibits excellent sonodynamic therapy effect, good biosafety, and good cancer treatment effect. In the preparation method of the composite material provided in the present invention, the copper-magnesium-aluminum hydrotalcite nanosheets are used as templates, and the copper-magnesium-aluminum hydrotalcite nanosheets are used as therapeutic drugs and carriers. The palladium source solution and the copper-magnesium-aluminum hydrotalcite nanosheet colloidal solution are mechanically stirred and then further impregnated with sodium borohydride for reduction and centrifugation to obtain the composite material. The process is simple, energy consumption is low, equipment requirements are low, and it is environmentally friendly. BRIEF DESCRIPTION OF THE DRAWINGS

[0034] The specific implementation modes of the present invention will be further described in detail below in conjunction with the accompanying drawings.

[0035] Figure 1 The transmission electron microscope image of the palladium nanocluster / hydrotalcite nanocomposite material synthesized in Example 1 is shown.

[0036] Figure 2 The X-ray diffraction spectrum of the palladium nanocluster / hydrotalcite nanocomposite material synthesized in Example 1 is shown.

[0037] Figure 3 The photothermal conversion curve of the palladium nanocluster / hydrotalcite nanocomposite material synthesized in Example 1 is shown.

[0038] Figure 4 The absorption spectrum of the palladium nanocluster / hydrotalcite nanocomposite material synthesized in Example 1 for detecting active oxygen using TMB as a probe is shown.

[0039] Figure 5 The absorption spectrum of the palladium nanocluster / hydrotalcite nanocomposite material synthesized in Example 1 for detecting singlet oxygen using DPBF as a probe is shown.

[0040] Figure 6 The singlet oxygen electron spin resonance image of the palladium nanocluster / hydrotalcite nanocomposite material synthesized in Example 1 is shown.

[0041] Figure 7 The NADH absorption spectrum of the palladium nanocluster / hydrotalcite nanocomposite material synthesized in Example 1 is shown. DETAILED DESCRIPTION

[0042] In order to more clearly illustrate the present invention, the present invention is further described below in conjunction with preferred embodiments and accompanying drawings. Similar components in the accompanying drawings are represented by the same reference numerals. It should be understood by those skilled in the art that the content specifically described below is illustrative rather than restrictive, and should not be used to limit the scope of protection of the present invention.

[0043] Example 1

[0044] A preparation method of a palladium nanocluster / hydrotalcite nanocomposite material comprises the following steps:

[0045] 1) Dissolve 19.849g magnesium nitrate hexahydrate, 0.934g copper nitrate trihydrate and 14.517g aluminum nitrate nonahydrate in 80mL water and mix well to obtain liquid A; dissolve 8.204g sodium carbonate in 50ml water and mix well to obtain liquid B; dissolve 9.6g sodium hydroxide in 160ml water and mix well to obtain liquid C; slowly add liquid A to liquid B under stirring in a water bath at 80°C, then add liquid C dropwise, adjust the pH to 9, mechanically stir and react for 30min at room temperature, centrifuge for 5min with a centrifuge at a speed of 8000-10000rpm / s, wash the precipitate with deionized water and anhydrous ethanol twice each, and centrifuge. Dry overnight in a drying oven at 60°C, grind and sieve, and the obtained blue powder is copper-magnesium-aluminum hydrotalcite with a molar ratio of 0.1:2:1.

[0046] 2) Take 1g of the copper-magnesium-aluminum hydrotalcite obtained in step 1) and dissolve it in 50ml of deionized water, and stir mechanically for about 30min. Dissolve 0.147g of sodium tetrachloropalladate in 20ml of deionized water, then add the dissolved sodium tetrachloropalladate solution to the evenly dispersed hydrotalcite nanosheet colloid, and continue stirring for 1h. Then add 0.71g of sodium borohydride (nNaBH4=40nPd 2+ ) was dissolved in 5 ml of deionized water and two drops of KOH (2M) were added, and then added dropwise to the mixed solution of sodium tetrachloropalladate and hydrotalcite, and immersed and reduced for 5 hours under stirring. After the reaction was completed, the mixture was centrifuged and washed (deionized water and ethanol 2 times each) with a centrifuge at a speed of 8000-10000 rpm / s. After separation, the precipitate was placed in a vacuum drying oven at 70°C and dried overnight, and then ground and sieved to obtain a palladium nanocluster / copper magnesium aluminum hydrotalcite nanocomposite material, wherein the loading amount of precious metal palladium on the hydrotalcite nanosheets was 5wt%.

[0047] In this embodiment, the transmission electron microscopy image of the prepared product palladium nanocluster / copper magnesium aluminum hydrotalcite nanocomposite material is as follows: Figure 1 shown. Figure 1 The composite material is a sheet structure with uniform size of 80-140nm. The XRD spectrum of the palladium nanocluster / copper magnesium aluminum hydrotalcite nanocomposite is shown in Figure 2, indicating that the palladium nanocluster / copper magnesium aluminum hydrotalcite nanocomposite was successfully synthesized. It was dispersed in water and irradiated with 808nm laser, such as Figure 3 As shown in the figure, the composite material exhibits excellent photothermal conversion ability and good photoacoustic imaging performance. After ultrasound, TMB and DPBF were used as probes and electron spin resonance images were used to test its acoustic dynamic effect. Figure 4 As shown, the characteristic absorption peak intensity of TMB at 652 nm was significantly enhanced with the extension of reaction time and the addition of ultrasound, showing a strong generation of reactive oxygen species; Figure 5 It is further seen that there is a characteristic absorption peak of DPBF at 410nm and the absorbance decreases significantly with the extension of reaction time, indicating that a large amount of singlet oxygen active oxygen species are generated (singlet oxygen can bleach the absorbance of DPBF at 410nm). Figure 6 As shown in Figure 2, the production of singlet oxygen was significantly increased after ultrasound, indicating that it has excellent sonodynamic properties. Figure 7 As shown, Figure 7 The NADH absorption spectrum of the prepared palladium nanocluster / hydrotalcite nanocomposite is shown. Figure 7 It can be seen that the composite material can further consume NADH and improve the cancer treatment effect biologically when used as a sonosensitizer or photoacoustic imaging agent.

[0048] Example 2

[0049] A preparation method of a palladium nanocluster / hydrotalcite nanocomposite material comprises the following steps:

[0050] 1) Dissolve 19.849g magnesium nitrate hexahydrate, 4.67g copper nitrate trihydrate and 14.517g aluminum nitrate nonahydrate in 80mL water and mix well to obtain liquid A; dissolve 8.204g sodium carbonate in 50ml water and mix well to obtain liquid B; dissolve 9.6g sodium hydroxide in 160ml water and mix well to obtain liquid C; slowly add liquid A to liquid B under stirring in a water bath at 80°C, then add liquid C dropwise, adjust the pH to 9, mechanically stir the reaction at room temperature for 30min, centrifuge for 5min with a centrifuge at a speed of 8000-10000rpm / s, wash the obtained precipitate with deionized water and anhydrous ethanol twice each, and centrifuge. Dry overnight in a drying oven at 60°C, grind and sieve, and the obtained blue powder is copper-magnesium-aluminum hydrotalcite with a molar ratio of 0.5:2:1.

[0051] 2) Take 1g of the copper-magnesium-aluminum hydrotalcite obtained in step 1) and dissolve it in 50ml of deionized water, and stir mechanically for about 30min. Dissolve 0.147g of sodium tetrachloropalladate in 20ml of deionized water, then add the dissolved sodium tetrachloropalladate solution to the evenly dispersed hydrotalcite nanosheet colloid, and continue stirring for 1h. Then add 0.71g of sodium borohydride (nNaBH4=40nPd 2+ ) was dissolved in 5 ml of deionized water and two drops of KOH (2M) were added, and then added dropwise to the mixed solution of sodium tetrachloropalladate and hydrotalcite, and immersed and reduced for 5 hours under stirring. After the reaction was completed, the mixture was centrifuged and washed (deionized water and ethanol 2 times each) with a centrifuge at a speed of 8000-10000 rpm / s. After separation, the precipitate was placed in a vacuum drying oven at 70°C and dried overnight, and then ground and sieved to obtain a palladium nanocluster / copper magnesium aluminum hydrotalcite nanocomposite material, wherein the loading amount of precious metal palladium on the hydrotalcite nanosheets was 5wt%.

[0052] The obtained palladium nanocluster / copper magnesium aluminum hydrotalcite nanocomposite material has a nanosheet size of 80-140nm. When dispersed in water, the composite material exhibits good photoacoustic imaging performance and excellent sonodynamic therapy effect.

[0053] Example 3

[0054] A preparation method of a palladium nanocluster / hydrotalcite nanocomposite material comprises the following steps:

[0055] 1) Dissolve 19.849g magnesium nitrate hexahydrate, 9.34g copper nitrate trihydrate and 14.517g aluminum nitrate nonahydrate in 80mL water and mix well to obtain liquid A; dissolve 8.204g sodium carbonate in 50ml water and mix well to obtain liquid B; dissolve 9.6g sodium hydroxide in 160ml water and mix well to obtain liquid C; slowly add liquid A to liquid B under stirring in a water bath at 80°C, then add liquid C dropwise, adjust the pH to 9, mechanically stir the reaction at room temperature for 30min, centrifuge for 5min with a centrifuge at a speed of 8000-10000rpm / s, wash the precipitate with deionized water and anhydrous ethanol twice each, and centrifuge. Dry overnight in a drying oven at 60°C, grind and sieve, and the obtained blue powder is copper-magnesium-aluminum hydrotalcite with a molar ratio of 1:2:1.

[0056] 2) Take 1g of the copper-magnesium-aluminum hydrotalcite obtained in step 1) and dissolve it in 50ml of deionized water, and stir mechanically for about 30min. Dissolve 0.147g of sodium tetrachloropalladate in 20ml of deionized water, then add the dissolved sodium tetrachloropalladate solution to the evenly dispersed hydrotalcite nanosheet colloid, and continue stirring for 1h. Then add 0.71g of sodium borohydride (nNaBH4=40nPd 2+) was dissolved in 5 ml of deionized water and two drops of KOH (2M) were added, and then added dropwise to the mixed solution of sodium tetrachloropalladate and hydrotalcite, and immersed and reduced for 5 hours under stirring. After the reaction was completed, the mixture was centrifuged and washed (deionized water and ethanol 2 times each) with a centrifuge at a speed of 8000-10000 rpm / s. After separation, the precipitate was placed in a vacuum drying oven at 70°C and dried overnight, and then ground and sieved to obtain a palladium nanocluster / copper magnesium aluminum hydrotalcite nanocomposite material, wherein the loading amount of precious metal palladium on the hydrotalcite nanosheets was 5wt%.

[0057] The obtained palladium nanocluster / copper magnesium aluminum hydrotalcite nanocomposite material has a nanosheet size of 80-140nm. When dispersed in water, the composite material exhibits good photoacoustic imaging performance and excellent sonodynamic therapy effect.

[0058] Example 4

[0059] Example 1 was repeated, except that the step 2) was replaced with "0.147 g of sodium tetrachloropalladate was dissolved in 20 ml of deionized water" by "0.276 g of sodium tetrachloropalladate was dissolved in 20 ml of deionized water", and "0.71 g of sodium borohydride (nNaBH4 = 40 nPd 2+ ) was dissolved in 5 ml of deionized water and replaced with 1.42 g of sodium borohydride (nNaBH4 = 40 nPd 2+ ) was dissolved in 5 ml of deionized water. The other conditions remained unchanged, and a palladium nanocluster / copper magnesium aluminum hydrotalcite nanocomposite with a loading of 10 wt% was prepared. The size of the obtained composite material was 80-140 nm. When it was dispersed in water, the composite material showed good photoacoustic imaging performance and excellent sonodynamic therapy effect.

[0060] Example 5

[0061] Example 1 was repeated, except that the step 2) was replaced with "0.553 g of sodium tetrachloropalladate was dissolved in 20 ml of deionized water" and "0.71 g of sodium borohydride (nNaBH4 = 40 nPd 2+ ) was dissolved in 5 ml of deionized water and replaced with 2.84 g of sodium borohydride (nNaBH4 = 40 nPd 2+ ) was dissolved in 5 ml of deionized water. The other conditions remained unchanged, and a palladium nanocluster / copper magnesium aluminum hydrotalcite nanocomposite with a loading of 20 wt% was prepared. The size of the obtained composite material was 80-140 nm. When it was dispersed in water, the composite material showed good photoacoustic imaging performance and excellent sonodynamic therapy effect.

[0062] Example 6

[0063] Example 2 was repeated, except that the step 2) was replaced with "0.147 g of sodium tetrachloropalladate was dissolved in 20 ml of deionized water" by "0.276 g of sodium tetrachloropalladate was dissolved in 20 ml of deionized water", and "0.71 g of sodium borohydride (nNaBH4 = 40 nPd 2+ ) was dissolved in 5 ml of deionized water and replaced with 1.42 g of sodium borohydride (nNaBH4 = 40 nPd 2+ ) was dissolved in 5 ml of deionized water. The other conditions remained unchanged, and a palladium nanocluster / copper magnesium aluminum hydrotalcite nanocomposite with a loading of 10 wt% was prepared. The size of the obtained composite material was 80-140 nm. When it was dispersed in water, the composite material showed good photoacoustic imaging performance and excellent sonodynamic therapy effect.

[0064] Example 7

[0065] Example 2 was repeated, except that the step 2) was replaced with "0.553 g of sodium tetrachloropalladate was dissolved in 20 ml of deionized water" and "0.71 g of sodium borohydride (nNaBH4 = 40 nPd 2+ ) was dissolved in 5 ml of deionized water and replaced with 2.84 g of sodium borohydride (nNaBH4 = 40 nPd 2+ ) was dissolved in 5 ml of deionized water. The other conditions remained unchanged, and a palladium nanocluster / copper magnesium aluminum hydrotalcite nanocomposite with a loading of 20% was prepared. The size of the obtained composite material was 80-140 nm. When it was dispersed in water, the composite material showed good photoacoustic imaging performance and excellent sonodynamic therapy effect.

[0066] Example 8

[0067] Example 3 was repeated, except that the step 2) was replaced with "0.147 g of sodium tetrachloropalladate was dissolved in 20 ml of deionized water" by "0.276 g of sodium tetrachloropalladate was dissolved in 20 ml of deionized water", and "0.71 g of sodium borohydride (nNaBH4 = 40 nPd 2+ ) was dissolved in 5 ml of deionized water and replaced with 1.42 g of sodium borohydride (nNaBH4 = 40 nPd 2+ ) was dissolved in 5 ml of deionized water. The other conditions remained unchanged, and a palladium nanocluster / copper magnesium aluminum hydrotalcite nanocomposite with a loading of 10 wt% was prepared. The size of the obtained composite material was 80-140 nm. When it was dispersed in water, the composite material showed good photoacoustic imaging performance and excellent sonodynamic therapy effect.

[0068] Example 9

[0069] Example 3 was repeated, except that the step 2) was replaced with "0.553 g of sodium tetrachloropalladate was dissolved in 20 ml of deionized water" and "0.71 g of sodium borohydride (nNaBH4 = 40 nPd 2+ ) was dissolved in 5 ml of deionized water and replaced with 2.84 g of sodium borohydride (nNaBH4 = 40 nPd 2+ ) was dissolved in 5 ml of deionized water. The other conditions remained unchanged, and a palladium nanocluster / copper magnesium aluminum hydrotalcite nanocomposite with a loading of 20 wt% was prepared. The size of the obtained composite material was 80-140 nm. When it was dispersed in water, the composite material showed good photoacoustic imaging performance and excellent sonodynamic therapy effect.

[0070] Example 10

[0071] Example 1 was repeated, except that the "immersion reduction for 5 h" in step 2) was replaced with "immersion reduction for 8 h". The other conditions remained unchanged, and a palladium nanocluster / copper magnesium aluminum hydrotalcite nanocomposite material was prepared. The size of the obtained composite material was 80-140 nm. When dispersed in water, the composite material exhibited good photoacoustic imaging performance and excellent sonodynamic therapy effect.

[0072] Comparative Example 1

[0073] The preparation method is basically the same as that in Example 1, except that the "PH controlled at 9" in 1) is replaced by "PH controlled at 7", and the other conditions remain unchanged, and no copper-magnesium-aluminum hydrotalcite nanosheets are obtained.

[0074] Comparative Example 2

[0075] The preparation method is basically the same as that in Example 1, except that "0.147 g of sodium tetrachloropalladate is dissolved in 20 ml of deionized water" in 2) is replaced by "0.147 g of palladium chloride is dissolved in 20 ml of deionized water", and the other conditions remain unchanged. No palladium nanocluster / copper magnesium aluminum hydrotalcite nanocomposite material is obtained.

[0076] Obviously, the above embodiments of the present invention are merely examples for clearly illustrating the present invention, and are not limitations on the implementation methods of the present invention. For ordinary technicians in the relevant field, other different forms of changes or modifications can be made on the basis of the above description. It is impossible to list all the implementation methods here. All obvious changes or modifications derived from the technical solution of the present invention are still within the protection scope of the present invention.

Claims

1. A palladium nanocluster / hydrotalcite nanocomposite material, characterized in that: The composite material comprises copper-magnesium-aluminum hydrotalcite nanosheets and palladium nanoclusters supported on the copper-magnesium-aluminum hydrotalcite nanosheets.

2. The composite material according to claim 1, characterized in that The composite material has a size of 80-140 nm and an average thickness of 6-8 nm; and / or The copper-magnesium-aluminum hydrotalcite nanosheets have a size range of 80-140 nm and a thickness of 1-3 nm and are layered double metal hydroxides; and / or The size of the palladium nanoclusters is 5-8 nm.

3. The composite material according to claim 1, characterized in that In the composite material, the loading amount of palladium nanoclusters on the copper-magnesium-aluminum hydrotalcite nanosheets is 5-25wt%.

4. The method for preparing the composite material according to any one of claims 1 to 3, characterized in that: The steps include: The copper-magnesium-aluminum hydrotalcite nanosheets and the aqueous solution of sodium tetrachloropalladate are mixed evenly, and then alkaline sodium borohydride is added dropwise. After mixing evenly, the mixture is centrifuged, washed, and dried to obtain the composite material.

5. The preparation method according to claim 4, characterized in that: The preparation of the copper-magnesium-aluminum hydrotalcite nanosheets comprises the following steps: Adding copper nitrate hexahydrate, magnesium nitrate trihydrate, aluminum nitrate nonahydrate and an aqueous solution of sodium hydroxide dropwise to an aqueous solution of sodium carbonate simultaneously, so that the pH of the mixed solution is maintained at 9-10; After stirring and reacting for 0.5-2h, the mixture is centrifuged, washed and dried to obtain the copper-magnesium-aluminum hydrotalcite nanosheets.

6. The preparation method according to claim 5, characterized in that: The molar mass ratio of the copper nitrate hexahydrate, the magnesium nitrate trihydrate and the aluminum nitrate nonahydrate is 0.1:2:1-1:2:

1.

7. The preparation method according to claim 4, characterized in that: The mass ratio of the copper-magnesium-aluminum hydrotalcite nanosheets to sodium tetrachloropalladate is 5-25%.

8. A sonosensitizer, characterized in that: The composite material is prepared from the composite material as claimed in any one of claims 1 to 3.

9. Use of the composite material according to any one of claims 1 to 3 in the preparation of sonosensitizers for tumor treatment.

10. Use of the composite material according to any one of claims 1 to 3 in the preparation of a photoacoustic imaging agent.